Atypical initial presentation of Takayasu arteritis as isolated supra-valvular aortic stenosis. Issue 1 (December 2016) - Kim, Do; Kim, Hwan
Abstract Background Among the vascular involvements of Takayasu arteritis, a supra-valvular aortic stenosis has been reported very rarely. We report a case of surgically corrected, supra-valvular aortic stenosis caused by Takayasu arteritis. Case presentation A 32-year-old female was diagnosed with supra-valvular aortic stenosis by transthoracic echocardiography for the evaluation of cardiac murmur with constitutional symptoms. Under the impression of non-familial sporadic type of supra-valvular aortic stenosis, surgical correction was performed. However, after 1 year from the operation, we could know the cause of her disease through the findings of computed tomographic aortography that Takayasu arteritis was suspected. Conclusions Takayasu arteritis should be considered in adult female patients presenting supra-valvular aortic stenosis with constitutional symptoms, even if no typical features of vascular involvement.